Відповідь:
Покрокове пояснення:
log_3 1=0 → x^2+2x+1<1 & x^2+2x+1>0
x^2+2x<0 & (x+1)^2>0 → x≠-1
x(x+2)<0
___+___-2___-___0+
хє(-2;-1)U(-1;0)
log_0.7 x+log_0.7(x+1)>=log_0.7(8-x)
log_0.7 x(x+1)>=log_0.7 (8-x)
x(x+1)=<8-x & x(x+1)>0 &8-x>0
x^2+x-8+x=<0 & хє(-inf; -1)U(0;+inf) & xє(-inf; 8)
x^2+2x-8=<0. & хє(-inf; -1)U(0;8)
x=-1±3
(x-3)(x+3)=<0
__+___-3___-___3___+__
хє[-3;3] & хє(-inf; -1)U(0;8)
хє[-3; -1)U(0;3]
Відповідь:
Покрокове пояснення:
log_3 1=0 → x^2+2x+1<1 & x^2+2x+1>0
x^2+2x<0 & (x+1)^2>0 → x≠-1
x(x+2)<0
___+___-2___-___0+
хє(-2;-1)U(-1;0)
log_0.7 x+log_0.7(x+1)>=log_0.7(8-x)
log_0.7 x(x+1)>=log_0.7 (8-x)
x(x+1)=<8-x & x(x+1)>0 &8-x>0
x^2+x-8+x=<0 & хє(-inf; -1)U(0;+inf) & xє(-inf; 8)
x^2+2x-8=<0. & хє(-inf; -1)U(0;8)
x=-1±3
(x-3)(x+3)=<0
__+___-3___-___3___+__
хє[-3;3] & хє(-inf; -1)U(0;8)
хє[-3; -1)U(0;3]